Traumatic Brain Injury and Covid-19 (Majalah Kedokteran Bandung, 2024)
Head trauma is a head injury caused by external forces in the head or body that results in disruption of the normal functioning of the brain. According to the CDC, deaths from head injuries were about 60,000 in 2016, and rose to more than 61,000 in 2017. The COVID-19 pandemic had caused poor non-COVID patient care, especially in low- and lower-middle-income countries with limited access to health facilities, resulting in increased morbidity and mortality, including among patients with head injuries. The purpose of this study was to understand the characteristics, duration of hospital stay, and difference of time to surgery interval in Traumatic Brain Injury patients in Dr. Hasan Sadikin General Hospital Bandung before and during the COVID-19 pandemic. This study was performed through analytical methods with a cross-sectional study design using analysis of medical records of head trauma patients treated in Dr. Hasan Sadikin General Hospital Bandung, Indonesia in the period before the pandemic (February 2018-February 2020) and during the pandemic (March 2020 - September 2021). Data analysis showed significant differences in length of hospitalization and operating intervals before and during the pandemic (p=0.04 and p=0.03), showing that there are differences in interval operation and duration of stay between patients with head trauma before the pandemic and during the pandemic.
Keywords: Comparative studies; COVID-19; traumatic head injury